2020
DOI: 10.1002/elan.202060315
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of Heterogeneous Affinity Behaviour of Methylene Blue and G‐quadruplex

Abstract: The heterogeneous binding behaviour between methylene blue (MB) and G‐quadruplex, one kind of single‐stranded (ss) DNA with specific guanine tetrads, has been thoroughly studied via electrochemical techniques. Positively charged MB interacted electrostatically with both G‐quadruplex and normal ssDNA but the binding and dissociation kinetics between them were significantly different. Compared with ssDNA, G‐quadruplex had a slower binding rate constant and dissociation rate constant with MB since there existed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For example, the hemin/G4, a known horseradish peroxidase mimicking DNAzyme, has been widely used in the construction of various electrochemical biosensors ( Wu et al, 2017 ; Liu et al, 2017b ; Chen et al, 2018 ; Sun et al, 2018 ; Ji et al, 2019 ; Wu et al, 2021a ). The discovery that the combination of G4 and MB can cause a great reduction in MB diffusion current has further expanded its biosensing application scope ( Zhang et al, 2014 ; Cao et al, 2017 ; Zhao et al, 2020b ). Subsequently, it was found that G-triplex (G3), as a folding intermediate of G4, has an even stronger affinity to MB than G4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the hemin/G4, a known horseradish peroxidase mimicking DNAzyme, has been widely used in the construction of various electrochemical biosensors ( Wu et al, 2017 ; Liu et al, 2017b ; Chen et al, 2018 ; Sun et al, 2018 ; Ji et al, 2019 ; Wu et al, 2021a ). The discovery that the combination of G4 and MB can cause a great reduction in MB diffusion current has further expanded its biosensing application scope ( Zhang et al, 2014 ; Cao et al, 2017 ; Zhao et al, 2020b ). Subsequently, it was found that G-triplex (G3), as a folding intermediate of G4, has an even stronger affinity to MB than G4.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, molecular dynamics simulations indicated that intercalation was the major mode of interaction between G3 and MB ( Zhao et al, 2019 ). Since the first report, the G3/MB composite has been proved to be an universal, simple, sensitive and efficient homogeneous signal readout element for electrochemical biosensors ( Zhao et al, 2020a ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%